Human Resource Management as a Strategic Driver of Digital Banking Transformation in the Open Banking Era: Evidence from Emerging Markets - Faisal Hasbullah Batubara (Jurnal Ilmiah Multidisiplin, 2025)
The digital transformation of the banking industry, accelerated by regulatory shifts toward Open Banking, presents both technological and human capital challenges. This study examines the role of Human Resource Management (HRM) in enabling the successful adoption of digital banking innovations in emerging markets. Using a mixed-methods approach, the research analyzes survey data from 120 banking professionals and conducts interviews with senior HR managers from five leading commercial banks. The findings reveal that HRM strategies focusing on competency development, change management, and ethical compliance significantly influence the success rate of Open Banking integration projects. Quantitative analysis indicates a positive correlation between digital skill readiness and the efficiency of API-enabled service rollouts, while qualitative insights highlight the importance of cultural transformation in overcoming resistance to change. The study offers theoretical contributions to the HRM and digital transformation literature, and practical implications for policymakers and financial institutions aiming to align human capital strategies with technological advancements.